Interior Design of Contemporary Triennial Art Museum with Terrace Theme: Case Study at Rice Field Areas in Sabrang Village, Delanggu. - Bilqis Sekarini Putri; Pandu Purwandaru (TAMA: Journal of Visual Arts, 2025)
The agricultural sector in Indonesia faces serious challenges, including the farmer regeneration crisis and the loss of local variety identity. Sabrang Village, with its rich agricultural potential, is the focus of revitalization. The contemporary triennial art museum is considered an appropriate strategy to attract tourists and revive the cultural value of agriculture. This design aims to design the interior design of a contemporary triennial art museum that can revitalize the agricultural area in Sabrang Village, increase the interest of the younger generation in the agricultural sector, preserve local cultural values ​​and identity, and become a forum for the development of contemporary art. The methodology used is qualitative with a case study approach. Data collection was carried out through observation, interviews, and literature studies. The data obtained were then analyzed descriptively to produce an interior design based on the context and objectives of the study. The results of the study produced an interior design concept with a terraced theme. The facilities designed include an exhibition area, workshop, public hall, office, merchandise store, and support area. This design is expected to create a dynamic, inspiring, and sustainable space, as well as a magnet for tourists and artists.